Analysis of Posture Using Posture Screening Mobile Application among Collegiates - S.F. Mariyam Farzana1 , Pooja2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
BACKGROUND: A posture is a position of the body which is maintained by the balanced muscular forceson the skeletal system. The posture is affected by the imbalance between the muscle force and also byreduction or increase in the muscle length. OBJECTIVE: To analyze the posture using posture screeningmobile application among collegiates. METHODOLOGY: It is a non-experimental, observational study,sample size 200 subjects both genders between 19 to 23 years, more than 18.5 to 25 ratios of BMI wereconveniently included in the study. The exclusion criteria was any congenital or acquired musculoskeletalproblems and recent surgeries fractures and injuries. METHOD: A written informed consent was takenfrom the subjects. The posture assessment was taken using posture screening mobile application and wasdocumented. RESULTS: The result shows the percentage of abnormal posture deviation among normalBMI collegiates. CONCLUSION: The study concluded that the prevention of musculoskeletal disordersamong young individuals with normal BMI is one of the challenging issues among health care professionals.